Multi-Faceted Anti-Cancer Mechanisms of Hesperidin Against Luminal A and Triple-Negative Breast Cancer Cells (Journal of Analytical Oncology, 2026)
Breast cancer remains a significant global health burden, compounded by issues of heterogeneity and treatment resistance, necessitating novel therapeutic strategies. Natural products, like the citrus flavonoid hesperidin, offer potential advantages. This study investigated the in vitro anti-cancer effects and mechanisms of hesperidin across diverse breast cancer cell lines (MCF-7, MDA-MB-231, 4T1) compared to normal human fibroblasts (HSF). Standard assays, including MTT, Trypan Blue, flow cytometry (cell cycle, Annexin V/PI apoptosis), wound healing, and qRT-PCR, were employed. Hesperidin induced dose-dependent cytotoxicity, exhibiting greater sensitivity in cancer cells versus HSF, particularly at lower concentrations. It triggered cell-type-specific cell cycle arrest (G1 in MCF-7, G2/M in MDA-MB-231, S-phase in 4T1/HSF) and significantly increased apoptosis in cancer cells, sparing HSF. Mechanistically, hesperidin modulated key gene expressions: upregulating apoptotic PTEN and CDH1 while downregulating anti-apoptotic HER2, EGFR, NOTCH1, and PALB. These findings demonstrate hesperidin's multi-faceted, selective anti-cancer activity in vitro, supporting its potential as a therapeutic candidate for breast cancer.